Frk positively regulates innate antiviral immunity by phosphorylating TBK1 - Zhang, Xiaomei; You, Ying; Xiong, Tingrong; Zhang, Xiaokai; Wang, Haibo; Geng, Jinxia; Wang, Miao; Xu, Yanyan; Gao, Shanshan; Wu, Xiaoyan; Zheng, Yue; Wen, Xianhua; et al. (Frontiers in Microbiology, 2025)
Type I interferons (IFN-I) are crucial for the initial defense against viral infections. TBK1 serves as a key regulator in the production of IFN-I, with its phosphorylation being essential for the regulation of its activity. However, the regulatory mechanisms governing its activation remain incompletely elucidated. In this study, we validated the function of Fyn-related kinase (Frk) in the antiviral innate immune response and identified the direct target molecule of Frk in the IFN-β signaling pathway. Furthermore, we elucidated the mechanism by which Frk phosphorylates TBK1 during infection and the role of Frk in IFN-β production. We discovered that Frk enhances the activation of the IFN-I production pathway by targeting TBK1. Mechanistically, Frk promotes the K63 ubiquitination of TBK1 and subsequent activation of the transcription factor IRF3 by phosphorylating TBK1 at tyrosine residues 174 and 179, thereby enhancing the production of IFN-β in macrophages. Employing both in vivo and in vitro viral infection assays, we demonstrated that IFN-β mediated by Frk inhibits the replication of VSV or HSV-1 and alleviates lung lesions. Our findings indicate that Frk functions as a key regulator of TBK1 to strengthen antiviral immunity and represents a promising target for the development of antiviral drugs.